The structure of affective fluctuations in a non-clinical sample - N. N. Osipova; L. M. Bardenstein; G. A. Aleshkina; E. V. Dmitrieva (Бюллетень сибирской медицины)
Aim. To study the structure of mood fluctuations at the preclinical stage based on the findings of screening methods.Materials and methods. A total of 129 students participated in the study. The average age was 18.95 ± 0.08 years. We used the clinical and psychopathological method, the Mini-International Neuropsychiatric Interview (MINI), and screening methods, such as the diagnostic questionnaire for bipolar disorder (Hypomania Checklist-32 (HCL-32)), and Hamilton Depression Scale (HAMD-17).Results. Upon a clinical and psychopathological examination according to ICD-10 criteria, class V, mental and behavioral disorders (F00-F99), including affective pathology, were not detected. According to the findings of the HCL-32 screening technique, 61.2% (n = 79) of respondents had a cumulative score above the threshold. Analysis of individual items on the HCL-32 scale across the entire sample revealed that the majority of examinees positively assessed the impact of mood elevations on the family sphere (63.57%; n = 82), social activities (68.99%; n = 89), work (75.19%; n = 91), and recreational sphere (82.17%; n = 106). Positive (36.43%; n = 47; 95% confidence interval (CI) 28.13–44.74) and neutral (37.21%; n = 48; 95% CI 33.35–50.37) assessments of mood elevations were also detected by the respondents’ immediate circle, which, in general, significantly complicates recognition of hypomania symptoms and delays seeking specialized care. In the structure of mood elevation episodes irritability (r = –0.684), conflict (r = –0.665), risk-taking behavior (r = –0.550), increased sexual desire (r = 0.527), increased energy and activity (r = 0.431), distractibility (r = –0.467), stimulant use (r = –0.467), and decreased need for sleep (r = 0.408) dominated. These signs are very similar to the clinical manifestations of a hypomanic episode in bipolar II disorder.Signs of mild depression revealed according to the HAMD-17 scale in 34.8% (n = 45) of respondents included sleep disorders (r = 0.693), decreased ability to work (r = 0.520), depressive mood (r = 0.579), hypochondria (r = 0.466), general somatic symptoms (r = –0.508), and gastrointestinal disorders (r = 0.513). These signs did not result in chief complaints and were not the reason for seeking specialized care.Conclusion. In the non-clinical sample, in the structure of mood swings, mood elevations dominated, which were not subjectively identified as illness symptoms and did not appear as complaints in clinical and psychopathological examinations. Low mood was accompanied by general somatic symptoms, which may indicate subsequent formation of comorbid pathology. The identified subsyndromal signs of hypomania and depression in the nonclinical sample in the absence of complaints and psychiatric care-seeking are of clinical significance as predictors of a bipolar affective disorder and require further clinical and dynamic monitoring.